Epidemiology and genotypes analysis of human papillomavirus infection in Huizhou, China - Shu, Zhun; Zhao, Wenli; Zhan, Xuebing; Zeng, Jiaqi; Li, Jingyi (Frontiers in Public Health, 2024)
Background: Human papillomavirus (HPV) is a main pathogenic factor for cervical carcinoma. The prevalence and genotypes distribution of HPV vary in different regions. Thus, our study aimed to investigate the epidemiology of HPV in Huizhou, China. Methods: HPV tests were detected in 5,325 female outpatients, we focused on the overall HPV prevalence, genotypes distribution, and the correlation of HPV genotypes with cervical cytology. Results: The overall HPV prevalence was 27.53%, HPV52, HPV58, HPV39, HPV16 and HPV51 were predominant genotypes with single infection rate of 70.80%. HPV infection rate showed a U-shaped age distribution, statistical differences were observed among 5 age groups (χ2 =50.497，P＜0.01), and the higher positive rate was aged under 30 (34.42%) and above 60 (34.74%). Among high-risk HPV (hrHPV) infections, 60.69% involved NILM, 0.99% HSIL. The degrees of cervical lesions in multiple hrHPV infections were worse than those in single infection (P<0.01). Conclusion: The HPV infection rate is high in Huizhou, Guangdong, single infection was predominant. HPV infection presented with a U-shaped age distribution. Multiple hrHPV infection was worrying since it may aggravate cervical lesions. Women should pay more attention to HPV detection and choose a more appropriate HPV vaccine according to local HPV type distribution.